THE INFLUENCE FINANCIAL LITERACY, FINANCIAL INCLUSION AND APPLICATION EMKM SAK TO MSME PERFORMANCE (CASE STUDY IN PANGURAGAN SUB-DISTRICT): - Putri Salmah; Itat Tatmimah; Muzayyanah; Saeful Huda Mubaarok; Mohamad Djadjuli (Jurnal Ekonomi, 2023)
Purpose of the study to analyze the effect of financial literacy, financial inclusion and the application SAK EMKM on the performance of UMKM in Panguragan District, Cirebon Regency. In this study, researchers also measured the level of financial literacy, financial inclusion and the application of SAK EMKM to UMKM in Panguragan . The research sample is the owners and managers of MSMEs Panguragan.  research uses quantitative methods. The data collection method purposive sampling and multiple linear regression analysis. The results of this study indicate that there is no effect of financial literacy on the performance of MSMEs and there is an effect of financial inclusion and the application of SAK EMKM on the performance of MSMEs. Simultaneously there is an influence between financial literacy, financial inclusion and the application of SAK EMKM on the performance of MSMEs. Variables of financial literacy, financial inclusion and implementation of SAK EMKM show a percentage of 42.1% and the remaining 57.9% is explained by other variables. The level of financial literacy, financial inclusion and the application of SAK EMKM to the performance of MSMEs in Panguragan is still relatively low.